PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS IV SDN BABBALAN - Tutik Kurniawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the impact of using Wordwall as a technology-based learning media on the Indonesian language learning outcomes of fourth-grade students at SDN Babbalan. The rapid development of educational technology provides opportunities to enhance student engagement in the classroom; however, challenges such as limited infrastructure and teachers' digital skills persist. This research uses a quantitative experimental approach with a One-Group Pretest-Posttest Design. The study was conducted with a sample of 25 students, focusing on comparing pretest and posttest results to measure improvements in Indonesian learning after the implementation of Wordwall. Data were collected through pretest and posttest scores, followed by normality testing using the Kolmogorov-Smirnov test, which showed normal distribution for both pretest and posttest (Sig. > 0.05). Homogeneity testing also indicated homogeneous data (Sig. > 0.05). Paired Sample T-Test results revealed a significant difference between pretest and posttest with a Sig. value < 0.001, indicating that Wordwall had a positive impact on students' learning outcomes. The average pretest score was 56.00, while the posttest score increased to 84.00. Additionally, the N-Gain analysis showed a value of 0.64, which falls within the moderate improvement category. This study recommends improving technology infrastructure in schools and providing continuous professional development for teachers to optimize the use of technology in education.  Keywords: Wordwall, Learning Media, Learning Outcomes, Indonesian Language, Elementary School